2009
DOI: 10.1017/s002531540999110x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of the sea urchinParacentrotus lividusin the Cantabrian Sea (northern Spain): environmental effects

Abstract: The main objective of this study was to describe the reproductive cycle of the sea urchin Paracentrotus lividus on the Cantabrian coast (north of Spain), and assess its relationship with environmental factors. To achieve this, samples were taken monthly from three localities during 17 months in two different habitats. At least 15 individuals from each location and habitat were collected during each sampling occasion and used for assessments of gonad index and histological sections. The water temperature and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…() and González‐Irusta, Goñi de Cerio, and Canteras () reported that gamete development started in winter and stopped in summer, suggesting a relationship between photoperiod and gametogenesis. Similarly, a single annual spawning episode in P. lividus during spring–summer was also observed in other populations from Portugal (Gago et al., ), Spain (González‐Irusta et al., ), France (Allain, ; Spirlet, Grosjean, & Jangoux, ), and Morocco (Bayed, Quiniou, Benrha, & Guillou, ), whereas shorter periods of gamete release in spring were recorded at other locations in Spain (Garmendia et al., ; Ouréns et al., ). Unlike the other Atlantic populations, sea urchins from Ireland spawned once at the end of summer (Byrne, ) or twice in spring and autumn (Crapp & Willis, ; Table ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…() and González‐Irusta, Goñi de Cerio, and Canteras () reported that gamete development started in winter and stopped in summer, suggesting a relationship between photoperiod and gametogenesis. Similarly, a single annual spawning episode in P. lividus during spring–summer was also observed in other populations from Portugal (Gago et al., ), Spain (González‐Irusta et al., ), France (Allain, ; Spirlet, Grosjean, & Jangoux, ), and Morocco (Bayed, Quiniou, Benrha, & Guillou, ), whereas shorter periods of gamete release in spring were recorded at other locations in Spain (Garmendia et al., ; Ouréns et al., ). Unlike the other Atlantic populations, sea urchins from Ireland spawned once at the end of summer (Byrne, ) or twice in spring and autumn (Crapp & Willis, ; Table ).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, several factors are responsible for variation in gamete induction in sea urchins, namely hydrodynamics (Soualili, ), turbulence (Pedrotti, ; Soualili, ), depth, photoperiod, temperature, habitat, food availability and quality (e.g. Gago et al., ; González‐Irusta et al., ; Ouréns et al., ; Spirlet et al., ), primary production and phytoplankton blooms (González‐Irusta et al., ; López et al., ; Starr, Himmelman, & Therriault, ), and population density (Ouréns et al., ). Moreover, because P. lividus is characterized as an opportunistic generalist, there is a wide range of adaptive and reproductive responses to environmental conditions throughout the species’ distributional range (Boudouresque & Verlaque, ; González‐Irusta et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…According to these authors, the variations observed from one locality to another in the time the GI reaches its annual maximum, are related more or less directly with the availability of food as indicated by Lawrence & Lane (1982). Differences in GI between locations are often observed (González-Irusta et al, 2010) and are also related to other factors such as farm effluents and organic pollution (Allain, 1975;Delmas & Régis, 1986;Cook & Kelly, 2007), temperature (Byrne, 1990), phytoplankton blooms (Lozano et al, 1995;Bayed et al, 2005) and salinity and contamination by heavy metals (Bayed et al, 2005). Considering the relationship with the availability of algal resources, we can compare the annual evolution of GI and RI.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal (gut) index relates the digestive system weight to the total wet body weight of the individual, indicating what proportion of this total weight is due to the gut (GII = wet weight of gut x 100/ wet body weight) and the repletion index (RI = wet weight of gut content x 100/ wet body weight) as has been used by Guillou & Michel (1994) and Privitera et al (2008). To assess gonadal condition we calculated the gonadosomatic (gonad) index (GI = wet weight of gonads x 100/ wet body weight), the usual approach adopted in other studies reported in the literature (Guettaf & San Martín, 1995;Sánchez-España et al, 2004;González-Irusta et al, 2010).…”
Section: Physiological Indicesmentioning
confidence: 99%
See 1 more Smart Citation